Different types and numbers metabolic abnormalities and risk of gallbladder stone disease in adults - Yang, Tingting; Zhong, Jianqin; Zhang, Renhua; Xiao, Fei; Wang, Yuan; Tao, Huimin; Hong, Feng (Frontiers in Nutrition, 2024)
Background: Metabolic abnormalities in the body increase the risk of gallbladder stones and their complications, which brings a great economic and social burden. The relationship between different types and amounts of metabolic abnormalities and gallstone risk in different sexes is poorly documented and controversial.Based on the baseline survey data of the Chinese Multi-Ethnic Cohort (CMEC) study, 4075 Chinese adults aged 30 to 79 years with complete abdominal ultrasound results and metabolic index data. Logistic regression model was used to evaluate the correlation between five metabolic abnormalities and gallstones, and to explore the gender difference.The detection rate of gallbladder stones was found to be 7.0%, with a higher rate in women (8.6%) than in men (4.1%). Logistic results showed adjustment odds ratio (ORs) and 95% confidence interval (95% CI) of dysglycemia + hypertension + central obesity in 3 metabolic combinations was 4.459 (1.653, 12.029). The four metabolic combinations, dysglycemia + dyslipidemia + hypertension + central obesity, dysglycemia + dyslipidemia + hypertension + abnormal blood uric acid and dysglycemia + dyslipidemia + central obesity + abnormal blood uric acid adjusted OR and 95%CI were 3.342 (1.459, 7.659), 5.439 (1.555, 19.018) and 2.971 (1.187, 7.435), respectively. Gender-stratified analysis found that "any three or more metabolic abnormalities and their components were associated with gallstone risk, more significantly in women.Conclusions: Different types and amounts of five metabolic abnormalities were associated with the risk of gallstone development, and the differences were more significant in women than men.